Unique TCR beta-subunit variable gene haplotypes in Africans. - Donaldson, I; Shefta, J; Lawson, C; Bushnell, JR; Morgan, A; Isaacs, J; Carpenter, D; Shaw, M; Rooth, I; Quinnell, R; Zumla, A; Ollier, W; et al. (2002)
This study investigated polymorphisms of genes in two regions of the T-cell antigen receptor beta-subunit (TCRB) locus, including BV9S2P, and BV6S7 in a 5' linkage group, and BV8S3, BV24S1, BV25S1, BV18S1, BV2S1, BV15S1 and BV3S1 in a 3' linkage group. These loci have been genotyped in individuals from five regions in Africa, including The Gambia, Nigeria, Cameroon, Tanzania, and Zambia, and in individuals from northern Britain, northern India, and Papua New Guinea (PNG). In the 3' linkage group, 11 unique haplotypes were identified in the combined African populations; two equally frequent haplotypes represent the majority of African chromosomes. One haplotype was found in all four regions studied. This is the most frequent haplotype in the northern British, northern Indian and PNG populations. Although present, it is infrequent in the African populations. A North-South gradient in the frequency of a common African haplotype was observed. The distribution did not represent that of a known disease. Evidence suggests that malaria is not responsible for selection of these haplotypes. Overall, this study highlights large differences in the genetic constitution of the TCRB locus between Africans and other populations.